How to Manage Value-Added Tax Refunds - Pessoa, Mario (IMF How To Notes; How-To Note ;, 2021)
The value-added tax (VAT) has the potential to generate significant government revenue. Despite its intrinsic self-enforcement capacity, many tax administrations find it challenging to refund excess input credits, which is critical to a well-functioning VAT system. Improperly functioning VAT refund practices can have profound implications for fiscal policy and management, including inaccurate deficit measurement, spending overruns, poor budget credibility, impaired treasury operations, and arrears accumulation.This note addresses the following issues: (1) What are VAT refunds and why should they be managed properly? (2) What practices should be put in place (in tax policy, tax administration, budget and treasury management, debt, and fiscal statistics) to help manage key aspects of VAT refunds? For a refund mechanism to be credible, the tax administration must ensure that it is equipped with the strategies, processes, and abilities needed to identify VAT refund fraud. It must also be prepared to act quickly to combat such fraud/schemes.